2010
DOI: 10.1038/npp.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

High-Novelty-Preference Rats are Predisposed to Compulsive Cocaine Self-administration

Abstract: Sensation/novelty-seeking is amongst the best markers of cocaine addiction in humans. However, its implication in the vulnerability to cocaine addiction is still a matter of debate, as it is unclear whether this trait precedes or follows the development of addiction. Sensation/novelty-seeking trait has been identified in rats on the basis of either novelty-induced locomotor activity (high-responder (HR) trait) or novelty-induced place preference (high-novelty-preference trait (HNP)). HR and HNP traits have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
306
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(340 citation statements)
references
References 65 publications
30
306
4
Order By: Relevance
“…The findings reported here are in contrast to those in outbred rats, for which there is no association between addiction liability and locomotor response to novelty (21,22,25,50). It is important to reiterate, however, that the bred lines exhibit differences in other traits that have been associated with addiction liability, including impulsivity (19), and these differences are not necessarily apparent in outbred LR/HR rats (22,23; see also ref.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The findings reported here are in contrast to those in outbred rats, for which there is no association between addiction liability and locomotor response to novelty (21,22,25,50). It is important to reiterate, however, that the bred lines exhibit differences in other traits that have been associated with addiction liability, including impulsivity (19), and these differences are not necessarily apparent in outbred LR/HR rats (22,23; see also ref.…”
Section: Discussioncontrasting
confidence: 54%
“…One prominent example is a study demonstrating that the diagnostic criteria for addiction could be modeled in rats (25). With the emergence of this animal model of "addiction," it was reported that locomotor response to novelty-or "sensation-seeking" as measured in the rat-is not associated with addiction liability per se (21,25,50), but does remain a good predictor of the initial propensity to take drugs (22,51). Although the design of the present study did not permit phenotypic differences to emerge in the acquisition of drug-taking behavior as it is typically assessed (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The rewarding properties of novelty have been documented in humans and animals (Bardo et al, 1989(Bardo et al, , 1996Besheer et al, 1999), and motivation for novelty predicts individual sensitivity to drug reward and reinforcement (Belin et al, 2011;Davis et al, 2008;Nadal et al, 2002;Pelloux et al, 2006;Piazza et al, 1989Piazza et al, , 2000Suto et al, 2001). We therefore suggest that the novel stimuli may have activated similar reinforcement and motivation processes as those involved in conditioned reinforcement-seeking behavior.…”
Section: Novelty Reinforcementmentioning
confidence: 84%
“…In addition, abnormal novelty-seeking behavior has been linked to many neuropsychiatric disorders. For example, high novelty-seekers are more susceptible to drugs of abuse than low novelty-seekers [51,52]. Reduced novelty-seeking is known to be associated with autism [6,7] and Alzheimer's disease [53].…”
Section: Discussionmentioning
confidence: 99%